Characterization of the distribution of platinum group elements in sulphide ores within the Merensky Reef at Modikwa and Two Rivers Platinum Mines, Eastern Bushveld Complex, South Africa - Zilibokwe, Nosibulelo Julie (Rhodes University, Faculty of Science, Department of Geology, 2017)
The distribution of the platinum group element (PGE), in the Merensky Reef was characterized by, first determining the occurrence of the platinum group minerals (PGM), then by establishing the PGE concentration in the base metal sulphides (BMS) associated with the PGE mineralization in the Merensky Reef from selected borehole intersections, at the Two Rivers (TRP) and Modikwa Platinum Mines in the Eastern Bushveld Complex. A mineral liberation analyser (MLA) was then used to identify the PGM phases; their silicate and base metal associations; and their grain size distribution. Electron microprobe quantitative analysis and mapping were then used to determine the compositional variation of the PGM and the PGE elemental distribution in the BMS, respectively. The study showed that the BMS including pyrrhotite, pentlandite, and chalcopyrite were the principal sulphides, where pyrrhotite was most prominent with minor quantities of pyrite. Orthopyroxene, clinopyroxene and plagioclase were the most abundant primary silicate minerals identified, while secondary silicates identified included talc, serpentine and amphibole. Platinum group minerals showed three distinct groups with respect to the mineralogical association with the PGE; (i) BMS association; (ii) chromite association; and (iii) silicate association. Of the BMS, chalcopyrite showed the most dominant association with the PGMs. All samples from both mines exhibited a wide range of PGMs, including maslovite, braggite, cooperate, laurite and PGE alloys such as ferroplatinum as well as other unidentified platinum and palladium sulphides, arsenides and bismuthides, while gold was present as electrum. The PGMs ranged in size from less than a micron to about 125 microns with an average of 20 microns. The close association of PGM with BMS along the margins of sulphides indicates that the PGMs were derived from the sulphide melt. PGE distribution in the sulphides at Modikwa showed pentlandite contained the highest concentrations of palladium (up to 379 ppm) and chalcopyrite hosting the highest rhodium concentrations (up to 793 ppm). Samples from Two Rivers revealed pentlandite as the principal host to both palladium and rhodium, with concentrations reaching up to 695 and 930 ppm, respectively. Magnetite at both Modikwa and Two Rivers showed significant rhodium content, reaching up to 982 and 930 ppm, respectively. The pyrrhotite compared to other sulphides contained all the elements found in the platinum group (PPGE), namely, platinum, palladium and rhodium, with all the platinum identified found in the pyrrhotite. The concentrations for the iridium group (IPGE) namely, iridium, osmium, and ruthenium were below the detection limit. The PGE mineralization in the stratigraphy varied within each mine. The mineralization revealed top loading in the central sector (Modikwa) and bottom loading in the southern sector (Two Rivers). The sequence of the Merensky Reef at the two sectors of the Eastern Bushveld Complex showed a remarkable similarity in their mineralogy suggesting that these two sectors were formed from the same liquid or formed simultaneously within a single magma chamber; however the PGE distribution within the stratigraphy may have been controlled by the presence of cumulate sulphides.
Keywords: Uncatalogued